Edukasi Kesehatan Gigi dan Mulut Melalui Media Pembelajaran Berbasis Interaktif pada Siswa SDN Inpres Tamamaung 4 Kota Makassar - Hasrini Hasrini; Dewi Sartika; Suciyati Sundu; Zahrawi Astrie Ahkam; Amirah Maritsa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Children who experience dental and oral health problems can experience a decline in quality. At the age of elementary school children, it is necessary for business actors to maintain dental and oral health regularly, both in counseling, examinations and dental and oral health care, by parents, schools and related government agencies. Elementary school age is the ideal time to train children's motor skills, including brushing their teeth. In addition, school age has shown learning sensitivity according to children's curiosity. Objective: To provide dental and oral health education through interactive learning media to students of SDN Inpres Tamamaung 4, Makassar City in 2022. Method: This community service is carried out by providing counseling, using media, namely back and forth worksheets, animated films, and puzzle games that aim to create two-way communication and make students active. Respondents in this community service were 3rd grade students of SDN Inpres Tamamaung 4, Makassar City in 2022. Results: There were 5 respondents (25%) with a good level of knowledge before being given facilities increasing to 14 (70%), there were 5 respondents (25%) with a sufficient level of knowledge before being given facilities decreasing to 4 (20%), and there were 10 respondents (50%) with a level of knowledge before being given facilities decreasing to 2 respondents (10%). Conclusion: Community service activities with the theme